Study on awareness, perceptions, experiences in decision process of hysterectomy in women presenting to Goa Medical College - Jindal, Manjusha; Naik, Viraj Ramesh; Sahasrabhojanee, Mrinalini; Cacodcar, Jagadish; Kulkarni, Manojkumar S.; Naik, Smita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Hysterectomy (removal of uterus) has many indications like fibroids, dysfunctional uterine bleeding, uterine prolapse and chronic pelvic pain. The purpose of this study is to know the level of awareness of women about hysterectomy, to study their experiences, to assess their involvement in decision making process and to develop a suitable protocol, counselling and education material to ensure women’s involvement. Methods: This is a cross sectional study using validated semi-structured interview questionnaire over 6 months (1st December, 2018 to 31st May, 2019) in Goa Medical College. Data was entered in epidata manager and analysed using SPSS 22 version. Categorical variables were expressed in percentages and proportions and quantitative variables in mean±SD. Significance was checked using Chi square test and association between dependent and independent variables was assessed by using bivariate analysis. P value <0.05 was taken as significant. Results: A total of 149 women were recruited into the study who were admitted for hysterectomy. The mean age of women was 49.3 years. The awareness with respect to various aspects of hysterectomy was good in 23.4% subjects and poor in 76.6% subjects. The awareness was significantly related to level of education (p=0.002), urban location (p=0.016) and socioeconomic status (p=0.028). Education was significant factor in decision-making process (p< 0.05). It was observed that good experience had positive correlation to their perception about hysterectomy. Conclusions: It was concluded that awareness about hysterectomy was significantly related to education, urban location and socio-economic status of women. Pre-operative education would help to reduce the post-operative symptoms for a women undergoing hysterectomy.